Personality traits and academic achievements of students - I A Novikova; N V Kargina (Peoples' Friendship University of Russia (RUDN University), 2009)
The problem of correlation of individually-typical peculiarities of personality traits (on the example of inquisitiveness, persistence and sociability) and specific of educational activity of students is examined in the article.